Cultural dynamics of gender-based violence and pastoral care in South Africa - Mudimeli, Lufuluvhi M. (HTS teologiese studies, 2024)
Gender-based violence is a prevalent issue that impacts most South Africans. The spread of sexual violence has created and atmosphere of intense fear in most homes. African cultural norms have helped to facilitate the continuation of discrimination against women. In African cultures, cases of abuse are often marginalised and considered an irrelevant reason for seeking a divorce. This has resulted in some women being forced to endure years of domestic abuse in their marriages, and they have even passed on this resilient mentality to more recent generations of married women. It is crucial to realise that the Recognition of Common Legislation Marriages Act, which is a part of South African legislation, acknowledges customs like polygamy and lobola. Lobola and polygamous marriages, among other practices, have been linked to major increases in the maltreatment of women, according to certain African researchers. In this particular study, the researcher aims to examine the impact of culturally induced gender-based violence (GBV) on pastoral care practices in South Africa, specifically focusing on the experiences and needs of South African women within abusive marriages. It is important to recognise that GBV is rooted in patriarchy, which promotes a culture of male power over women. In this research, qualitative methods will be employed to investigate how this unhealthy power dynamic encourages men to behave violently towards women.Contribution: This study delves into the intricate relationship between culturally induced GBV and pastoral care in South Africa. Focused on the surge in violence, it employs qualitative methods to explore women’s experiences, revealing the connection between violence and entrenched patriarchal structures. The research seeks to inform and enhance pastoral practices in addressing GBV.